2010
DOI: 10.1063/1.3488609
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of bimolecular recombination by UV-sensitive electron transport layers in organic solar cells

Abstract: Incorporating UV-sensitive electron transport layers (ETLs) into organic bulk heterojunction (BHJ) photovoltaic devices dramatically impacts short-circuit current (Jsc) and fill factor characteristics. Resistivity changes induced by UV illumination in the ETL of inverted BHJ devices suppress bimolecular recombination producing up to a two orders of magnitude change in Jsc. Electro-optical modeling and light intensity experiments effectively demonstrate that bimolecular recombination, in the form of diode curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Optical properties of each material layer are determined via spectroscopic ellipsometry, 14 which closely match reported values. 15,20 Layer thicknesses are measured with cross-section scanning electron microscopy and verified with profilometry and by fitting simulations of the spectral reflection to the measured reflection by varying layer thicknesses. 21 To model electrical performance, G is used as input in a drift/diffusion effective medium model of the active layer with Ohmic contacts 22 implemented in COMSOL MULTIPHYS-ICS.…”
Section: Methodsmentioning
confidence: 99%
“…Optical properties of each material layer are determined via spectroscopic ellipsometry, 14 which closely match reported values. 15,20 Layer thicknesses are measured with cross-section scanning electron microscopy and verified with profilometry and by fitting simulations of the spectral reflection to the measured reflection by varying layer thicknesses. 21 To model electrical performance, G is used as input in a drift/diffusion effective medium model of the active layer with Ohmic contacts 22 implemented in COMSOL MULTIPHYS-ICS.…”
Section: Methodsmentioning
confidence: 99%
“…Metal oxides such as zinc oxide (ZnO),11–15 titanium oxide (TiO x )16–18 and aluminium oxide (Al 2 O 3 )19 have been widely investigated as electron extraction layers (EEL) in inverted organic solar cell devices. In particular ZnO has drawn special interest due to its beneficial properties such as high conductivity and transparency, as well as the simplicity and low cost of solution processing 9, 12, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the resistance of TiO x decreases after UV illumination. 12 Therefore, we first consider the possibility that this strong dependence of resistance on bias and UV exposure is governed by the change of bulk resistivity in the TiO x layer alone. From in-plane resistivity measurements on TiO x films, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high dielectric constants of MoO 3 29 and TiO x , 30 under reverse bias the electrical potential drops predominantly within the P3HT:PCBM layer. We estimate the work function of MoO 3 , which is insensitive to UV illumination, 12 to be 5.3 eV. 31 The formation of a d-hole layer between MoO 3 and the P3HT allows the formation of an ohmic contact, illustrated by the dipole layer D in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation